Corruption, Growth, and the Environment : A Cross-Country Analysis - Heinz Welsch (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
The relationship between per capita income and a number of pollution indicators has been found to display an inverted U-shaped or downward-sloping pattern. Corruption may affect this relationship in two distinct ways: by raising pollution at given income levels (direct effect) and by reducing per capita income (indirect effect). The total effect is ambiguous a priori. Using cross section data for several indicators of pollution, the paper estimates the direct and the indirect effect of corruption on pollution. The indirect effect via income is positive or negative depending on the income level. If negative, the indirect effect is dominated by the positive direct effect. Overall, our measures of pollution are monotonically increasing in corruption. Because this relationship is particularly strong at low income levels, developing countries can considerably improve both their economic and environmental performance by reducing corruption.
Keywords: O1; K4; Q2; 330; corruption; growth; pollution; environmental Kuznets curve; Umweltbelastung; Wirtschaftswachstum; Sozialprodukt; Korruption; Umweltschutz; Theorie; Welt